Internal Control on the Revenue Cycle at Discuss Space & Coffee Cafe Jember - Meiba Ayumy Subroto, Meiba Ayumy Subroto; Venantya Asmandani, Venantya Asmandani; Chandra Setiawan Tri Yuwono, Chandra Setiawan Tri Yuwono (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
Discuss Space & Coffee is a cafe that not only provides a place to gather but also to work. This research was conducted to evaluate the implementation of the accounting system in the revenue cycle and identify weaknesses and limitations of existing internal controls. The research method used was qualitative, incorporating interviews and direct observation as data collection techniques.The results show that although the accounting system in the revenue cycle has been implemented, there are still some obstacles, especially those originating from bugs in the majoo application. These obstacles interfere with the process of recording revenue in real-time. However, the owner of Discuss Space & Coffee has overcome this problem in an effective and efficient way, namely by adding additional alternative tools to ensure smooth operations. To overcome bugs in the majoo application, it is recommended that the application manager immediately make regular updates and improvements. In addition, technical training for cafe staff can also help reduce the impact of technical glitches that may occur in the future.